2012
DOI: 10.1186/2049-6958-7-44
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of regional lung aeration determined by electrical impedance tomography in patients with acute respiratory distress syndrome

Abstract: BackgroundLung tissue of patients with acute respiratory distress syndrome (ARDS) is heterogeneously damaged and prone to develop atelectasis. During inflation, atelectatic regions may exhibit alveolar recruitment accompanied by prolonged filling with air in contrast to regions with already open alveoli with a fast increase in regional aeration. During deflation, derecruitment of injured regions is possible with ongoing loss in regional aeration. The aim of our study was to assess the dynamics of regional lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
3
25
0
1
Order By: Relevance
“…Therefore, to mitigate VALI, investigators have attempted to more accurately measure important mechanical parameters of the lung such as e. Our results demonstrate that e RS decreased with increasing PEEP, an observation that has been previously documented and which was due to increased EELV RS in our experiment (Blankman et al 2016). More important than the fact that the techniques described in our study allow the measurement of e RS , is the ability to observe regional e. Heterogeneity in regional e has previously been observed using methods such as CT scans, electrical impedance plethysmography and forced oscillation techniques (Kaczka et al 2011b;Pulletz et al 2012;Wolf et al 2013;Cressoni et al 2014;da Paula et al 2016). We found that varied widely, with the highest strain lobes exposed to approximately threefold the strain of the lowest strain lobes (Fig.…”
Section: Global and Regional Strain With Frisupporting
confidence: 83%
“…Therefore, to mitigate VALI, investigators have attempted to more accurately measure important mechanical parameters of the lung such as e. Our results demonstrate that e RS decreased with increasing PEEP, an observation that has been previously documented and which was due to increased EELV RS in our experiment (Blankman et al 2016). More important than the fact that the techniques described in our study allow the measurement of e RS , is the ability to observe regional e. Heterogeneity in regional e has previously been observed using methods such as CT scans, electrical impedance plethysmography and forced oscillation techniques (Kaczka et al 2011b;Pulletz et al 2012;Wolf et al 2013;Cressoni et al 2014;da Paula et al 2016). We found that varied widely, with the highest strain lobes exposed to approximately threefold the strain of the lowest strain lobes (Fig.…”
Section: Global and Regional Strain With Frisupporting
confidence: 83%
“…58 The high scan rates allow the assessment of intratidal changes in regional C rs. 38 Another EIT measure of respiratory mechanics is the regional respiratory time constant 4459…”
Section: Eit Measuresmentioning
confidence: 99%
“…Major heterogeneities in regional ventilation in diseases like ARDS,44 66 COPD,42 62 lung cancer76 or cystic fibrosis77 can be traced by EIT. The effects of ageing can also be detected 16…”
Section: Clinical Use Of Eit In Adult Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it provides information about the side effects of mechanical ventilation enhanced by some diseases, i.e. ARDS, COPD, lung cancer, cystic fibrosis or ageing-associated processes [38][39][40]. Electrical impedance tomography has also been used to detect pleural oedema [41,42], changes in respiratory parameters after aspiration [43] and to evaluate onelung ventilation [44].…”
Section: Discussionmentioning
confidence: 99%